2013
DOI: 10.1152/advan.00095.2012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an individual readiness assurance test on a team readiness assurance test in the team-based learning of physiology

Abstract: We examined whether requiring an individual readiness assurance test (iRAT) before a team readiness assurance test (tRAT) would benefit students in becoming better problem solvers in physiology. It was tested in the form of tRAT scores, the time required to complete the tRAT assignment, and individual performance on the unit examinations. Students in one section were given the iRAT at the beginning of the team-based learning session. The same set of questions was given to students as their tRAT immediately aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 13 publications
0
25
0
2
Order By: Relevance
“…Carbrey et al found that performance on a knowledge test after traditional in-class RATs was equal to having learners complete the iRAT at home without a tRAT (25). Another study by Gopalan et al found that although the iRAT helps teams earn higher tRAT scores, it does not affect students' examination scores (26). The eTBL method skips full administration of the RAT, allowing for a more time-efficient administration of TBL.…”
Section: Discussionmentioning
confidence: 99%
“…Carbrey et al found that performance on a knowledge test after traditional in-class RATs was equal to having learners complete the iRAT at home without a tRAT (25). Another study by Gopalan et al found that although the iRAT helps teams earn higher tRAT scores, it does not affect students' examination scores (26). The eTBL method skips full administration of the RAT, allowing for a more time-efficient administration of TBL.…”
Section: Discussionmentioning
confidence: 99%
“…Students who completed the iRAT scored better on the gRAT and completed it more quickly compared to students who only took the gRAT. However, there was no difference in performance on course exams [ 7 ]. In another study, the group application exercise was not graded.…”
Section: Discussionmentioning
confidence: 99%
“…Gopalan et al suggested that the tRAT combined with the iRAT is a more effective approach of TBL than the tRAT alone. 11 So in this study, we adopted both iRAT and tRAT as defined previously by Gopalan et al…”
Section: Discussionmentioning
confidence: 99%